The Value of Different Single or Combined Indexes of the Captopril Challenge Test in the Diagnosis of Primary Aldosteronism - Xiang, Qiao; Chen, Tao; Yu, Kai; Li, Yuanmei; Li, Qianrui; Tian, Haoming; Ren, Yan (Frontiers in Endocrinology, 2021)
Objective: The result interpretation of the captopril challenge test (CCT) for the diagnosis of primary aldosteronism (PA) is not standardized. Superiorities of different indexes in the CCT have not been fully investigated. We aimed to comprehensively evaluate the value and influence factors of different CCT-associated indexes in the diagnosis of PA. Methods: We enrolled 312, 85, 179 and 97 patients in the groups of PA, essential hypertension (EH), unilateral PA (UPA) and bilateral PA (BPA), respectively. For each single index investigated, we computed diagnostic estimates including the area under the receiver operating characteristic curve (AUC). We performed pre-specified subgroup analyses to explore influence factors. We assessed the diagnostic value of combined indexes in binary logistic regression models. Results: Post-CCT aldosterone to renin ratio (ARR) (AUC=0.8771) and plasma aldosterone concentration (PAC) (AUC=0.8769) showed high value in distinguishing PA from EH, and their combination (AUC=0.937) was even superior to either alone. The diagnostic efficacy was moderately high for post-CCT aldosterone to angiotensin II ratio (AA2R) (AUC=0.834) or plasma renin activity (PRA) (AUC=0.795) but low for the suppression percentage of PAC (AUC=0.679). Post-CCT PAC had a significantly higher AUC in the UPA than BPA subgroup (AUC=0.914 vs 0.827, P＜0.05). Conclusion: We can take post-CCT ARR and PAC altogether into account to distinguish PA from EH, while caution should be taken to interpret CCT results with the suppression percentage of PAC. Post-CCT PAC may perform better to identify the unilateral than bilateral form of PA.